Chronic diarrhea in west highland white terrier caused by hyperthyroidism - Maulana ArRaniri Putra; Isnin Ramadhani Nafiu; Diah Pawitri (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2019)
A 8-years old, female West Highland White Terrier, with a 7-month history of diarrhea and sometimes hematemesis, polyuria and polydipsia. The antibiotic, antihelminthic, antiprotozoal, vitamin and diet changing was given by the previous veterinarian, diarrhea was stopped for a while but the diarrhea reappear. The clinical symptoms was chronic diarrhea, polyuria, and polydipsia. Physical examination revealed a swelling in ventrolateral neck area suspected a enlarge thyroid gland in right side. Blood analyses performed a markedly elevated thyroxine (T4) level and increased alkaline phosphatase (ALP). An urinalysis revealed decreases specific gravity (hypostenuria). From an examination, the diagnose hyperthyrodism has been made. The dog was treated by unilateral thyroidectomy. Histopathology of thyroidectomy was thyroid adenoma. A month after surgery, diarrhea was gone and polyuria and polydipsia was better